Origin and history of the beaver introduction in South America - Pietrek, Alejandro G. (2014)
The introduction of the North American beaver (Castor canadensis) to Tierra del Fuego is a widely known example of a successful biological invasion. However, the origin and history of this introduction bears closer scrutiny. Using historical documentation we provide evidence that beaver introduction occurred as a single release event of 20 beavers from northern Manitoba, Canada. This not only clarifies the origin of the invasion, but also suggests that the beaver population of Patagonia descends from a smaller number of individuals than previously assumed.